1997
DOI: 10.1007/bf02406063
|View full text |Cite
|
Sign up to set email alerts
|

General assessment of the occurrence of keratinolytic fungi in river and marine beach sediments of Catalonian waters (Spain)

Abstract: Abstract. Sediments from 8 river mouths of the Catalonian coast (Spain) were examined for keratinolytic fungi. Out of 1250 river and marine samples examined, 499 (39.9%) were positive for these fungi. Aphanoascus fulvescens (anamorph + teleomorph), Chrysosporium keratinophilum, Ch. tropicum, Ch. an. of Arthroderma curreyi, Ch. pannieola, Ch. europae and Ch. indicum were the predominant species in the sediments. River samples were rich in keratinolytic fungi, whereas in marine beach sediments they occurred spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…In our study other filamentous fungi with keratinophilic activity were also found. (Vidal et al, 1966), Spain (Ulfig et al, 1997) and Italy (Salvo and Fabianno, 2007), among others.…”
Section: Discussionmentioning
confidence: 99%
“…In our study other filamentous fungi with keratinophilic activity were also found. (Vidal et al, 1966), Spain (Ulfig et al, 1997) and Italy (Salvo and Fabianno, 2007), among others.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses of the fungal populations were based on the following indicators: the number of appearances, frequency (% of the total number of colonies), and L index (number of strains divided by the number of Petri dishes) following the method of Ulfig et al (1997). For the filamentous fungi, we also counted the number of taxa isolated and their percentage prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The fungi in beach sediments has been rarely studied, though some saprophytes in this community have been shown to behave as human pathogens or opportunistic pathogens, especially in immunocompromized or sensitive patients (Kern and Blevins, 1997). Keratinolytic fungi such as Chrysosporium and Trichophyton, which are known agents of human and animal infections, have been isolated from beach sand (Ulfig et al, 1997). Furthermore, the species and populations of microorganisms that are present in beach sediments appear to be correlated with the presence of human users of the beach (Papadakis et al, 1997;Arvanitidou et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Samples were transported in a refrigerated container and immediately processed in the laboratory. Samples were shaken vigorously in the same containers and, after leaving them for 1 min to settle, the water was decanted, and the sediment poured onto several layers of sterile filter paper on plastic trays to remove any water excess (Ulfig et al 1997). To isolate a wide range of fungal species, each sample was cultured as follows: 1 g of sediment was distributed across three Petri dishes and mixed with dichloran rose-bengal-chloramphenicol agar (DRBC; 2.5 g peptone, 5 g glucose, 0.5 g KH2PO4, 0.25 g MgSO4, 12.5 mg Rose Bengal, 100 mg chloramphenicol, 1 mg dichloran, 10 g agar, 500 mL distilled water) melted at 45 °C; and in parallel, another 1 g was distributed in three other Petri dishes and mixed with melted potato dextrose agar (PDA; Pronadisa) supplemented with 2 g/L of chloramphenicol and 2 g/L of cycloheximide.…”
Section: Sampling and Fungal Isolationmentioning
confidence: 99%